Sexually dimorphic serotonergic dysfunction in a mouse model of Huntington's disease and depression. - Thibault Renoir (Public Library of Science (PLoS), 2011)
Depression is the most common psychiatric disorder in Huntington's disease (HD) patients. In the general population, women are more prone to develop depression and such susceptibility might be related to serotonergic dysregulation. There is yet to be a study of sexual dimorphism in the development and presentation of depression in HD patients. We investigated whether 8-week-old male and female R6/1 transgenic HD mice display depressive-like endophenotypes associated with serotonergic impairments. We also studied the behavioral effects of acute treatment with sertraline. We found that only female HD mice exhibited a decreased preference for saccharin as well as impaired emotionality-related behaviors when assessed on the novelty-suppressed feeding test (NSFT) and the forced-swimming test (FST). The exaggerated immobility time displayed by female HD in the FST was reduced by acute administration of sertraline. We also report an increased response to the 5-HT(1A) receptor agonist 8-OH-DPAT in inducing hypothermia and a decreased 5-HT(2A) receptor function in HD animals. While tissue levels of serotonin were reduced in both male and female HD mice, we found that serotonin concentration and hydroxylase-2 (TPH2) mRNA levels were higher in the hippocampus of males compared to female animals. Finally, the antidepressant-like effects of sertraline in the FST were blunted in male HD animals. This study reveals sex-specific depressive-related behaviors during an early stage of HD prior to any cognitive and motor deficits. Our data suggest a crucial role for disrupted serotonin signaling in mediating the sexually dimorphic depression-like phenotype in HD mice.